2020
DOI: 10.3390/cancers12030743
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the Impact of Cancer Treatment Modalities on Circulating Tumor Cells (CTCs)

Abstract: The metastatic cascade consists of multiple complex steps, but the belief that it is a linear process is diminishing. In order to metastasize, cells must enter the blood vessels or body cavities (depending on the cancer type) via active or passive mechanisms. Once in the bloodstream and/or lymphatics, these cancer cells are now termed circulating tumor cells (CTCs). CTC numbers as well as CTC clusters have been used as a prognostic marker with higher numbers of CTCs and/or CTC clusters correlating with an unfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 165 publications
(190 reference statements)
0
7
0
Order By: Relevance
“…EMT and its different intermediate status have recently been noticed as crucial drivers of tumor progression and metastasis (16,24,25). In light of recent research demonstrated that the CTC count could be used as a prognostic biomarker, and a higher CTCs count may predict an unfavourable prognosis in malignant patients (26)(27)(28)(29)(30). In this research, we used the Canpatrol ™ CTC filtration platform to detect CTCs in different EMT statuses intend to explore their prognostic assessment value.…”
Section: Discussionmentioning
confidence: 99%
“…EMT and its different intermediate status have recently been noticed as crucial drivers of tumor progression and metastasis (16,24,25). In light of recent research demonstrated that the CTC count could be used as a prognostic biomarker, and a higher CTCs count may predict an unfavourable prognosis in malignant patients (26)(27)(28)(29)(30). In this research, we used the Canpatrol ™ CTC filtration platform to detect CTCs in different EMT statuses intend to explore their prognostic assessment value.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that local cancer therapy, such as surgery and radiotherapy, can potentially mobilize tumour cells into the systemic circulation and potentially influence the risk of development of distant metastatic disease, is not novel. Several surgical studies have reported an increase in CTC counts during and/or after oncological surgery in patients [18-23]. With regards to radiotherapy, although not demonstrated in human studies until more recently, Kaplan and Murphy [24], in 1949, showed that lung metastases were more common in tumour-bearing mice that received radiotherapy than those were not irradiated.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in NSCLC there was no association between CTCs and long-term survival of the patients observed (Barr et al, 2020). While mechanisms of "classical" metastasis cascade are well-studied (Dianat-Moghadam et al, 2020), there is a gap of knowledge of the mechanisms of post-surgical invasion of the secondary tissue by the CTCs, as current knowledge about CTCs biology is very limited (Mathias et al, 2020). The mechanisms of the postsurgical CTCs wound implantation and local migration into the secondary tissue (often not involving entry into the bloodstream) potentially leading to the metastasis within the surgical scars are undoubtedly different compared to "classical" metastasis, because of the alteration in the composition and structure of the surgically damaged target tissue (for example, disrupted basal membrane), the influence of the post-surgical inflammatory milieu, as well as specific phenotypic characteristics of the post-surgical CTCs clusters (for example, difference in the level of expression of EMT markers by CTCs, stromal cell composition within the CTCs, and others).…”
Section: Introductionmentioning
confidence: 99%